Frekuensi Kegagalan Pengisian Saluran Akar dengan Teknik Preparasi Step Back pada Gigi Berakar Ganda di Rumah Sakit Gigi dan Mulut Universitas Jember 2011-2016 (The Frequency of Failure Root Canal Filling with Step Back PreparationTechnique on Multiple Ro - Melisa Novitasari; Raditya Nugroho; Sulistiyani . (Pustaka Kesehatan, 2017)
Background: Most of root canal preparation use step back technique which form the root canal. Thecool lateral condensation technique is a standard technique taught to students, which has the highestcure rate between 87% - 94% and a root canal filling was ended by 0-2 mm from the radiographic apex,which the underfilling cure rate between 68% - 77% and the overfilling cure rate between 75% -76%.Some research suggests that the molars teeth had the highest frequency of failure in root canal filling.Objective: To identify the frequency of failure in root canal filling with preparation step back techniqueson a double-rooted teeth Dental Hospital of the University of Jember from 2011 until 2016. Methods: Thedesign of this study is a descriptive by gathering medical records. The radiograph pictures of doublerootedteeth which underfilling and overfilling were evaluated by researcher, data was calculated withmanual furthermore data was displayed in tables and graphics. Results and Conclusions: Teeth withunderfilling of 68 teeth larger than teeth that overfilled a total of 18 teeth. The maxillary teeth with themost underfilling are the teeth 14 and the tooth mandibular 46 where as the most overfilled teeth in themaxilla are the teeth 26 and the mandibular is the tooth 46. The percentage of root canal treatmentunderfilling and overfilling is 27.3% Overall number of patients with multiple root canal treatment.Keywords: lateral condensation, overfilling, step back, underfilling